Nordic measures to promote sustainable aviation fuels: Artikel - Kristensen, Niels Buus; Ydersbond, Inga Margrete; Thune-Larsen, Harald (Proceedings from the Annual Transport Conference at Aalborg University, 2021)
Decarbonising transportation is necessary to reach long-termed climate goals and Nordic countries have committed themselves to be ambitious and lead the way. Finding technically feasible and economically viable solutions for aviation is among the most difficult challenges. This paper examines opportunities for increased Nordic cooperation to promote use of sustainable aviation fuels. Pros and cons of implementing each of five policy instruments in a Nordic context are analyzed and their impacts in terms of impact on air travel, CO2-emissions and Government budget are estimated. The paper concludes that the most suitable common Nordic policy for significant CO2 reductions from air travel is to announce a gradually increasing blend-in share of sustainable fuels toward 2030 backed by establishing a Nordic fund that will compensate the price premium compared to fossil fuels. The fund should be financed by common earmarked passenger taxes for all departing flights from the Nordics.